HUBUNGAN DUKUNGAN KELUARGA, TEMAN SEBAYA, DAN KEAKTIFAN KONSELING KOMUNITAS DENGAN KESEHATAN MENTAL REMAJA - Sandy, Lilis Lela; Yuningsih, Yuni; Kusnawan, Aep; Miharja, Sugandi (Jurnal Visi Ilmu Pendidikan, 2026)
This study aims to analyze the relationship between family support, peer support, and community counseling engagement with adolescent mental health. This study uses a quantitative approach that utilizes correlational methods to define and analyze the relationship between two or more variables, without inferring cause and effect. Participants in this study consisted of 1,887 students of a State Islamic Senior High School in Serang Regency. The sample size was 330 students, drawn using the Slovin formula. This study yielded four main findings: 1) There is a correlation between family support and the mental health of school-age adolescents. 2) There is a correlation between peer acceptance and the mental health of school-age adolescents. 3) There is a correlation between active participation in community counseling and the mental health of school-age adolescents. 4) There is a simultaneous correlation between the level of family support, peer acceptance, and active participation in community counseling and the mental health of school-age adolescents. The findings of this study provide theoretical implications for the development of guidance and counseling science and adolescent developmental psychology